2009
DOI: 10.1243/14680874jer02108
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of mixture formation and in-cylinder combustion processes in direct injection diesel engines using group-hole nozzles

Abstract: Mixture properties of the transient fuel spray injected by group-hole nozzles were quantitatively studied in a constant volume chamber via the laser absorption scattering (LAS) technique, and compared with conventional single-hole nozzles. Specific areas investigated included non-evaporating and evaporating ambient conditions, and the conditions of free spray and spray impinging on a flat wall. The particular emphasis was on the effect of one of the key parameters of the group-hole nozzle structure, namely, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The BSFC of the clusters is generally lower than that of the reference nozzle for both the piston bowl geometries. The clusters are regarded as a promising approach to lower fuel consumption at early injection timing because the sprays from clusters have a greater mass of entrained ambient gas and greater mass of fuel vapour than the reference nozzle [16,18]. In the PCCI condition, HC and carbon monoxide (CO) emissions are of major concern, because HC and CO emissions are usually higher with lower combustion temperatures.…”
Section: Premixed Charge Compression Ignitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BSFC of the clusters is generally lower than that of the reference nozzle for both the piston bowl geometries. The clusters are regarded as a promising approach to lower fuel consumption at early injection timing because the sprays from clusters have a greater mass of entrained ambient gas and greater mass of fuel vapour than the reference nozzle [16,18]. In the PCCI condition, HC and carbon monoxide (CO) emissions are of major concern, because HC and CO emissions are usually higher with lower combustion temperatures.…”
Section: Premixed Charge Compression Ignitionmentioning
confidence: 99%
“…The penetration length and atomization increase for cluster nozzles with higher injection pressures [16,17]. Gao et al [18] have performed engine visualization studies using Fig. 1 Re-entrant bowl shape and shallow-dish bowl shape parallel and diverging group-hole nozzles.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research works have been performed on the influence of in-cylinder mixture formation and combustion process on the outcome of exhaust emissions from an internal combustion engine [1][2][3]. It is well proven that homogeneous mixture results in lower particulate emission from diesel engines [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Uchida et al 1 reported the combined effects of combustion chamber geometry and swirl ratio on the emission characteristics. Gao and et al 2 studied the effects of a group-hole nozzle spray to achieve both fine droplet atomization and enough spray penetration. By improving air utilization in the cylinder, it is possible to improve both soot emissions and fuel consumption.…”
Section: Introductionmentioning
confidence: 99%